Are physical inactivity, sitting time and screen time associated with obstructive sleep apnea in adults? A cross-sectional study - Rafael Mathias Pitta; Bruno Gion Cerazi; Luana Queiroga; Raphael Mendes Ritti Dias; Marco Túlio de Mello; Fernando Henpin Yue Cesena; Roberta Luksevicius Rica; Julien Steven Baker; Marcio Sommer; Gabriel Grizzo Cucato; Danilo Sales Bocalini; Oskar Kauffman (São Paulo Medical Journal, 2022)
Abstract BACKGROUND: Sitting time, screen time and low physical activity (PA) levels have been associated with several diseases and all-cause mortality. PA is related to better sleep quality and absence of daytime sleepiness, along with lower risks of obstructive syndrome apnea (OSA). However, studies on the relationship between sitting time, screen time and OSA are scarce in the literature. OBJECTIVE: To analyze associations between PA levels, sitting time, screen time and OSA among adults with suspected sleep disorder. DESIGN AND SETTING: Cross-sectional study conducted at Hospital Israelita Albert Einstein. METHODS: Data were collected from 369 adults with suspected sleep disorders who visited the hospital’s neurophysiology clinic between August 2015 and January 2017. RESULTS: Correlations between hypopnea and PA indicators were demonstrated for total sitting time (0.123; P = 0.019) and total screen time (0.108; P = 0.038). There was also a correlation between latency for rapid-eye-movement sleep (REM_LAT) and total sitting time (0.103; P = 0.047) and a negative correlation between mean oxyhemoglobin saturation (SaO_Avg) and total PA time (-0.103; P = 0.048). There were no associations between PA parameters and apnea-hypopnea index. After adjusting for confounding factors (body mass index, age and gender), sitting time and screen time were not associated with OSA. CONCLUSION: After adjusting for anthropometric and clinical factors, excessive sitting time or screen time was not associated with OSA in adults suspected of sleep disorders. Age, gender, hypertension, body mass index and waist circumference were associated with OSA.